Komunikasi Antarpribadi Kepala Dusun dalam Upaya Vaksinasi Masyarakat di Desa Tanjung Selamat - Dilla, Rumiati; Vita, Nadra Ideyani; Sahputra, Dedi (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
The purpose of this study was to find out the experience of the hamlet head in conveying information related to the Covid-19 vaccine, to find out how interpersonal communication was used by the hamlet head in conveying information on the Covid-19 vaccine and to find out what were the obstacles to the hamlet head in conveying information regarding vaccines. Covid-19. This research uses qualitative methods with a phenomenological approach. The data collection techniques used by observation, interviews, and documentation. The data analysis technique used in this study is a qualitative descriptive analysis technique. While testing the validity of the data is done by using source triangulation. Based on the experience of the hamlet head, there are still many Tanjung Selamat villagers who do not believe in the existence of Covid-19 and do not want to vaccinate. Interpersonal Communication can run well when conveying information regarding the Covid-19 vaccine and getting feedback verbally and non-verbally on the grounds that some people in Tanjung Selamat Village do not want to carry out the Covid-19 Vaccination, but there are also obstacles when conducting Interpersonal Communication to the communicant because the communicant (community) does not believe in the existence of Covid-19